Enlarged perivascular spaces and cognitive impairment after stroke and transient ischemic attack. Issue 1 (January 2018) - Arba, Francesco; Quinn, Terence J; Hankey, Graeme J; Lees, Kennedy R; Wardlaw, Joanna M; Ali, Myzoon; Inzitari, Domenico; ,
Background: Previous studies suggested that enlarged perivascular spaces are neuroimaging markers of cerebral small vessel disease. However, it is not clear whether enlarged perivascular spaces are associated with cognitive impairment. We aimed to determine the cross-sectional relationship between enlarged perivascular spaces and small vessel disease, and to investigate the relationship between enlarged perivascular spaces and subsequent cognitive impairment in patients with recent cerebral ischemic event. Methods: Anonymized data were accessed from the virtual international stroke trial archive. We rated number of lacunes, white matter hyperintensities, brain atrophy, and enlarged perivascular spaces with validated scales on magnetic resonance brain images after the index stroke. We defined cognitive impairment as a mini mental state examination score of ≤26, recorded at one year post stroke. We examined the associations between enlarged perivascular spaces and clinical and imaging markers of small vessel disease at presentation and clinical evidence of cognitive impairment at one year using linear and logistic regression models. Results: We analyzed data on 430 patients with mean (±SD) age 64.7 (±12.7) years, 276 (64%) males. In linear regression analysis, age (β = 0.24; p  < 0.001), hypertension (β = 0.09; p  = 0.025), and deep white matter hyperintensities (β = 0.31; p  < 0.001) were associated with enlarged perivascular spaces. In logistic regression analysis, basal ganglia enlarged perivascular spaces were independently associated with cognitive impairment at one year after adjusting for clinical confounders (OR = 1.72, 95% CI = 1.22–2.42) and for clinical and imaging confounders (OR = 1.54; 95% CI = 1.03–2.31). Conclusions: Our data show that in patients with ischemic cerebral events, enlarged perivascular spaces are cross-sectionally associated with age, hypertension, and white matter hyperintensities and suggest that enlarged perivascular spaces in the basal ganglia are associated with cognitive impairment after one year.